Long-term Care Responsibility and its Opportunity Costs - Annika Meng (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
This paper analyzes the relationship between long-term care provision and the average individual wage rate. In addition, the effects of the number of hours spent on caregiving on the probability of employment as well as on the number of hours worked are examined. Data from the Survey of Health, Ageing and Retirement (SHARE) of 2004 and 2006 is used to analyze caregiving effects on the European labor market. Descriptive statistics show a positive correlation between hours of care and the wage rate for those working. In the regression analysis, sample-selection models combined with instrumental-variable estimation are used to estimate the causal effects of hours of care on wages. The results illustrate that care for parents has a large negative impact on the individual's wage rate. Test results show that controlling for sample selection is reasonable. Finally, the probability of employment is only decreased in the female sample. Although the hours worked are not significantly affected. – – Dieses Papier analysiert die Beziehung zwischen Langzeitpflege und dem durchschnittlichen individuellen Lohnsatz potenzieller Pflegepersonen. Außerdem wird der Effekt von pflegestunden auf die Wahrscheinlichkeit, Arbeit anzubieten, sowie auf die Anzahl der Arbeitsstunden untersucht. Daten des Survey of Health, Ageing and Retirement (SHARE) aus den Jahren 2004 und 2006 werden genutzt, um Effekte auf dem europäischen Arbeitsmarkt zu analysieren. Deskriptive Statistiken zeigen eine positive Korrelation zwischen Pflegestunden und Lohnsatz für arbeitende Pflegepersonen. In der Regressionsanalyse werden Selektionsmodelle mit Instrumentenvariablenmethoden kombiniert, um kausale Effekte dazu zu erhalten. Die Ergebnisse veranschaulichen, dass die Pflege von Eltern einen stark signifikant negativen Effekt auf den individuellen Lohnsatz hat. Testergebnisse zeigen, dass es notwendig ist, für Stichprobenselektion zu kontrollieren. Die Wahrscheinlichkeit, Arbeit anzubieten, wird nur in einer Stichprobe aus Frauen gesenkt. Die Arbeitsstunden werden nicht signifikant beeinflusst.
Keywords: J11; J22; C01; 330; Informal care; labor-market outcomes; sample selection; Familienpflege; Opportunitätskosten; Lohn; Erwerbsverlauf; EU-Staaten